PERAN CAHAYA MONOKROMATIK PADA PROFIL DARAH ITIK PITALAH DAN PERTAMBAHAN BOBOT BADAN YANG DIBERI KUNYIT (CURCUMA LONGA L.) SEBAGAI FEED ADITIF - Ulvira Rifni; Sabrina Sabrina; Kusnadidi Subekti; Rusfidra Rusfidra; Firda Arlina (Wahana Peternakan, 2023)
This study aims to determine to what extent, the role of monochromatic light then being fed turmeric additives has an impact on the blood profile and body weight gain of Pitalah ducks. The material used was 100 Pitalah ducklings. The method used was an experiment with the Split Plot method arranged in a Randomized Block Design (RBD). The treatment started on day 15 and the duration of the study was 10 weeks. The treatment given is the main plot factor is monochromatic lighting consisting of yellow light as a control, blue, red, green. Subplot factor, namely turmeric consisting of B1: 18 gr and B2: 16 gr. The experimental results showed that the interaction between factor A (light) and factor B (turmeric) had no significant effect (P>0.05) on blood profile and body weight gain in Pitalah ducks. The conclusion of this study is that the administration of monochromatic light (yellow, blue, red, green) with turmeric levels (18 gr and 16 gr) has no interaction on blood profile (leukocytes & erythrocytes) and body weight gain in pitalah ducks. In this condition, leukocyte values ​​ranged from 18.39 to 73.51 (103 /mm-3 ) and erythrocyte values ​​from 18.39 to 73.5 (103 /mm-3 ), both of these values ​​were in a less normal range so that it can be indicated that the health condition of the ducks is not prime. Subsequently, body weight gain was obtained 63.58 - 78.16 grams/tails/week. Keywords: Monochromatic light, turmeric, blood profile, body weight gain and Pitalah ducks